Cognitive prosthethics : health industrialization set - Derian, Maxime (ISTE Press Ltd ; Elsevier Ltd, 2018)
Prosthetic Digital Devices in the Human Body provides a synthetic point-of-view on the different possibilities offered by these implantable tools. Implanting a digital device to provide healthcare isn't just science-fiction anymore. Since the first pacemakers were surgically implanted in humans 60 years ago, there has been a significant increase in the different types of digital devices added to the body for eHealth purposes. This book comprehensively covers the latest technologies and their applications.